Estimation of Repeatability Value of Weaning Weight and Most Probable Producing Ability (MPPA) of Saburai Doe in Tanggamus Regency - Kusuma Adhianto; Tri Isngatirah; Sulastri Sulastri; Muhammad Dima Iqbal Hamdani (Buletin Peternakan, 2019)
The aim of this study was to estimate the value of repeatability of weaning weight and Most Probable Producing Ability (MPPA) value of Saburai Doe in village breeding center (VBC), located in Tanggamus Regency. This research was conducted in Sumberejo and Gisting districts in January to May 2018.  Data collected in this study included the recording data of kids’ birth, birth weight, weaning age, weaning weight, offspring sex from 122 doe who have given birth twice from 2015 to 2017.  The study was carried out by using survey method to know weaning weight, estimated repeatability values, and MPPA values of Saburai doe in Sumberejo and Gisting district. Results of this research shows that the average corrected weaning weight of Saburai Doe in Sumberejo and Gisting district were 16.59±3.45 and 16.93±2.90, with the repeatability value were 0.76 and 0.59 (high category), respectively. The result also shows that the average value of MPPA of Saburai Doe were 16.59±2.98 and 16.93±2.15, respectively. There were 10 doe with the highest MPPA value consisting of 5 does from Sumberejo district K2 22.07, Y3 21.95, Y4 21.80, K1 21.39, AD3 21.38 and 5 does from Gisting District D3 22.03, B1 21.09, D4 20.98, A1 20.83, D5 20.74. It is suggested to select Saburai Doe with the best MPPA to improve productivity of Saburai Doe for the next generation.